Primary care clinic-based chronic disease care: features of successful programs. - O'connor P; Sperl-Hillen J; Pronk N; Murray T (Disease Management & Health Outcomes, 2001)
Objective: To identify common features of primary care clinics that have successfully achieved improvement in chronic disease care. Methods: We analyzed seven primary care practices that have achieved significant improvement in chronic disease care provided to adults with diabetes mellitus, hypertension, lipid disorders, or heart disease. Strategies used to improve care were mapped across categories of the Enhanced Primary Care (EPC) model, and common features were identified. Results: The seven practices achieved significant improvement in health outcomes of adults with diabetes mellitus, hypertension, or lipid disorders within 1 to 2 years. Outcome measures typically included all people in the practice with the conditions of interest. Improvement was sufficient to substantially reduce risk of major cardiovascular events by over 20% on a population basis. In the majority of successful primary care practices, combinations of ten key strategies were used: leadership; resources; clinical guidelines; organized care teams; patient activation; information systems; identification of population at risk; monitoring; prioritization; and active outreach to patients. Conclusions: The results support the existence of an EPC model capable of achieving significant improvements in chronic disease care over a relatively short period of time. Health systems and primary care practices interested in improving the care of patients with chronic diseases may consider simultaneous use of the various improvement strategies identified in this study.